Pendampingan Perhitungan Harga Pokok Produksi Dan Penentuan Harga Jual Produk Umkm Nisda Cemilan Pangan Lokal - Jasmadeti, Jasmadeti; Nadidah, Nadidah (Jurnal Abdimas Dedikasi Kesatuan, 2024)
Determining the selling price of a product is very important for a company because it affects the profits and losses obtained by the company. Profits in a company are obtained from the selling price of the product which can cover the costs incurred in producing the product. Calculating the cost of production is a way to determine the right selling price for a company. The cost of production is the total costs incurred during the production process to process raw materials into products that are ready to be sold. The aim of this research is to determine the calculation of the cost of production of Egg Rolls at the UMKM Nisda Snacks Local Food calculations in determining the selling price of Egg Rolls. It is known that in calculating the cost of production, the company takes into account direct labor costs which are not in accordance with cost accounting standards and several other cost elements which are not taken into account in calculating the cost of production. The results of this research show that the cost of production of Egg Rolls at UMKM Nisda Local Food Snacks not yet in accordance with cost accounting standards so that the selling price set is lower than the selling price calculated according to cost accounting standards. The calculation of the cost of production carried out by UMKM Nisda Local Food Snacks is not yet detailed. The selling price calculation used by UMKM Nisda Snacks Local Food is also still not correct, which causes the company to experience deficiencies in charging the cost of production which has an impact on determining the selling price which is lower than what was actually expected. Keywords: Cost Accounting, Cost of Goods Production, Selling Price.